2016 28th Euromicro Conference on Real-Time Systems (ECRTS) 2016
DOI: 10.1109/ecrts.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Parallelism without Exploding Deadlines in a Mixed Criticality Embedded System

Abstract: Complex embedded systems today commonly involve a mix of real-time and besteffort applications. The recent emergence of small low-cost commodity UMA multicore processors raises the possibility of running both kinds of applications on a single machine, with virtualization ensuring that the best-effort applications cannot steal CPU cycles from the real-time applications. Nevertheless, memory contention can introduce other sources of delay, that can lead to missed deadlines. In this research report, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…We characterize the intensity of memory behavior with the bandwidth to shared memory, as it is fairly common, notably in regulation systems such as MemGuard [2] or the approach proposed by Blin et al [3]. We use the counters provided by the Performance Monitoring Unit (PMU) of the MMDC to measure it.…”
Section: A Quantitative Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…We characterize the intensity of memory behavior with the bandwidth to shared memory, as it is fairly common, notably in regulation systems such as MemGuard [2] or the approach proposed by Blin et al [3]. We use the counters provided by the Performance Monitoring Unit (PMU) of the MMDC to measure it.…”
Section: A Quantitative Characterizationmentioning
confidence: 99%
“…An alternative approach is proposed by Blin et al [3] to keep under a specified threshold the slowdown caused by best efforts application to a real-time one. In this approach, an interference model of the hardware platform is built using measures.…”
Section: Interference Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Automotive industry is increasingly adopting multicores as the reference computing solution for ECUs [1][2][3]. Yet, several academic and industrial studies show that multicores have disruptive effects on Validation and Verification (V&V) practice, shaped on singlecore architectures: timing analysis techniques have to be carefully adapted to factor in multicore contention in WCET estimates [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been observed that the memory usage of applications running on one core may impact the execution time of applications running on the other cores [19,21]. In recent work [13], we have shown that sharing these resources implies that the operations initiated on a best-effort core can affect the duration of real-time tasks running on other cores. In that work, we have developed an approach to address the memory induced slowdown that uses run-time monitoring to detect when the interference risks causing the real-time task to exceed its deadline beyond a threshold that is considered to be tolerable.…”
Section: Introductionmentioning
confidence: 99%